Deep Brain Stimulation during Pregnancy and Delivery: Review of Current Literature - Baláž, Marek; Búřil, Jiří; Kunst, Jonáš; Hrabovský, Dušan; Hajda, Šimon; Chrastina, Jan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Deep brain stimulation (DBS) is an established method in the treatment of not only Parkinson's disease motor complications but also dystonia and tremor, and there are data supporting the efficacy of DBS in epilepsy and some psychiatric problems. The alleviation of the neurologic problems may enable females of childbearing age to consider pregnancy because of being able to take care of their child. The aim of the study is to provide a review of the data available on the effect of DBS on the course of pregnancy and delivery in patients suffering from diseases amenable for DBS treatment (Parkinson's disease, dystonia, obsessive compulsive disorder, Tourette's syndrome, epilepsy). Although data available in the literature on pregnancy and childbirth in patients with an implanted active DBS system are limited to small case series and case reports, the number of younger patients implanted with DBS systems will potentially require more attention beyond specialized DBS centers. In emergency deliveries, general obstetricians and neurosurgeons should be provided with a protocol to prevent injuries to the implanted system with potentially devastating consequences for the patient.
Keywords: deep brain stimulation; pregnancy; Parkinson's disease; dystonia; epilepsy